Performance evaluation of the earliest deadline first policy over ad hoc networks. (27th August 2012) - Korbi, I. El; Saidane, L. Azouz
To satisfy the Quality of Service (QoS) requirements of delay–sensitive flows, we propose in this paper to support the Earliest Deadline First (EDF) policy over wireless ad hoc networks. Hence, we enhance the IEEE 802.11 protocol to support the real–time EDF scheduling policy. Therefore, we develop a Markov–chain–based analysis modelling the backoff process of the EDF policy. Then, we propose to evaluate the performance of EDF in terms of saturation throughput and service time delay bounds. Service time delay bounds are obtained by inverting service time Z–transforms. Analytical results are validated and extended by simulation using the NS–2 network simulator. Finally, we evaluate the performance of the EDF policy in a multi–hop environment in the presence of ad hoc routing protocols.